Embedded implementation of phase imbalance faults in three-phase inverters: The impact of MOSFET conduction resistance variations - Oussama Idbouhouch; Mourad Zegrari; Nabila Rabbah; Ibtihal Ait Abdelmoula; Hicham Oufettoul; Saad Motahhir (Results in Engineering)
This work investigates the phase unbalance failures occurring on three-phase inverter, especially related to the variation of the Ron conduction resistance of the silicon carbide (SiC) MOSFET. These failures, caused by component degradation, aging, or thermal stress, affect the inverter performance, leading to voltage imbalance, higher harmonic distortion, and reduced stability. Three fault scenarios were evaluated: an increase in Ron's value in a single MOSFET, a pair of MOSFETs in the same inverter leg, and two MOSFETs in separate legs. This study used MATLAB Simulink as a simulation tool and integrated Model in the loop (MIL), Software in the loop (SIL) and processor in the loop (PIL) testing with Space Vector Pulse Width Modulation (SVPWM) control technique, performed on an STM32 microcontroller. The simulations indicate the considerable variation in phase voltages, currents, and the total harmonic distortion (THD) for each scenario. Results from SIL and PIL are consistent with those obtained from MIL simulation, therefore validating the robustness of the control algorithm through different testing stages. The comparative analysis emphasizes the distinct impacts of localized and distributed faults on inverter stability and performance. The analysis presents important contribution towards understanding the dynamics of the fault, thus supporting development of robust control schemes and fault tolerant designs of three-phase inverters in renewable energy and industrial applications.